Restaurant analytics: Emerging practice and research opportunities. Issue 10 (8th August 2022) - Roy, Debjit; Spiliotopoulou, Eirini; de Vries, Jelle
Abstract: Smart technologies and increased data availability enable restaurateurs to gather more information about customers and their behavior. These data can be combined with data from other sources to make a wide range of strategic and operational restaurant decisions, and can therefore generate tremendous value for restaurants and their customers. This study focuses on discussing the most promising research opportunities in restaurant operations that leverage data analytics. In particular, we focus on specific research questions across restaurant decision domains such as location, reservation and table management, queue management, menu design and engineering, and multichannel order management. For each research question, we motivate its practical and theoretical relevance, identify data sources, propose a methodological approach for analysis, and discuss actionable insights for practitioners. As a result, this paper aims to highlight data analytics opportunities for restaurateurs and inspire researchers to contribute in this domain.